O papel da indústria de transformaç\~ao e das exportaç\~oes de manufaturas no processo de desenvolvimento dos países de Renda Média - Nelson Marconi; Cristina Fróes de Borja Reis; Eliane Cristina de Araújo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The aim of this paper is to evaluate the role of the manufacturing sector in the development process through the first two laws of Kaldor. The first states that the higher the growth of industrial output, more significant is the growth rate of the product of the economy as a whole. The second law, known as the Kaldor-Verdoorn law, establishes a deterministic relation between growth of manufacturing productivity and output growth in the manufacturing sector. Additionally, it is tested the influence of manufactured exports in this process, given its importance as a source of autonomous demand and as a factor that relaxes the constraint to growth, and the relevance of the exchange rate, because it is assumed that its level influences exports of such products. Therefore, initially the article will present the behavior of manufacturing and exports in the recent past, more specifically since 1990, highlighting some stylized facts on the economic performance of countries according to the level of income, changes in investment rates, the centrality of manufacturing and exports of manufactures. Afterwards, it is performed a theoretical reflection on the importance of manufacturing and exports of manufactured goods to the process of economic development and a discussion on the role of the exchange rate and the systematization of a Kaldorian model to assess the importance of manufacturing and its exports to the development.
Keywords: O11; O14; O40; L60; 330; economic development; international trade; manufacturing sector; middle-income countries